Analysis Of The Digital Marketing Strategy Of Healthy Juice In Ulul Ilmi Msmes Using NVIVO - Akhirson, Armaini; Apriyanti, Rehulina; Riswanti, Sri; Saputra, Guntur Eka; Tua, Robert Managem (Ilomata International Journal of Management, 2025)
This study aims to evaluate the digital marketing strategy for Healthy Juice products in Ulul Ilmi MSMEs with a SWOT analysis method supported by NVivo software. The data used in this study was obtained from primary sources, namely the interviews and observations of Ulul Ilmi MSME owners, and secondary data from the results of the collection of media articles related to this research. Using NVivo facilitates secondary data analysis in media articles relevant to digital marketing topics, allowing for more in-depth identification of patterns and themes—data analysis techniques to identify data and digital marketing strategies using the SWOT Matrix. The findings from this research analysis indicate that Ulul Ilmi MSMEs have the main strengths in product quality and the ability to innovate, which can be used to expand market reach through digital strategies. Significant opportunities are found in the increasing health trends among the public and the ease of access to marketing through digital platforms. However, this research also reveals weaknesses in mastery of digital technology and the threat of increasingly fierce competition. By utilizing NVivo, this study successfully identified digital marketing strategies that MSMEs can implement to optimize market potential and strengthen competitiveness.